Digital Transformation and the Proliferation of Fake News: Analyzing the Impact of Social Media - Dr. Sandhya Sharma Mr. Girish Kumar Singh Mr. Anurag Singh Dr. Rusha Mudgal Dr. Pooja Rana (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The transformation of legacy media into digital platforms marks a significant shift in how news is created and consumed. In the digital era, the internet and social media have democratized the dissemination of information, offering unprecedented access and engagement. However, this shift also brings challenges, as these platforms can easily become conduits for misleading and fake news. The proliferation of smartphones and widespread Wi-Fi access have made platforms like Facebook, Instagram, YouTube, and Twitter influential in news delivery and entertainment. In countries such as the USA and India, leaders like the President and Prime Minister use Twitter to directly interact with voters and supporters, impacting governmental operations and public discourse. This direct engagement underscores the growing influence of web journalism and public media. In addition to this, communication tools such as Skype, WhatsApp, Messenger, and LINE have facilitated the rapid spread of information, including fake news. This paper employs empirical research methods to examine the rise of fake news during the COVID-19 pandemic. Data from credible sources, such as Reality Check and official portals, inform the research questions. The study draws on primary and secondary sources to identify instances of fake news on social media and assesses its adverse effects on society. It also offers technical strategies for recognizing and combating fake news.Catchphrases: Digitalization, Facebook, Counterfeit News, Web, Virtual Entertainment.